Plan estratégico para incrementar las ventas de la empresa mueblería Reyes Suárez Samuel del cantón Santa Elena de la provincia de Santa Elena, año 2015 - Carrera Recalde, Rosa Graciela (2016)
The research is framed to make a strategic plan aimed at increasing sales in the company Mueblería Reyes Suarez Samuel Canton Santa Elena in the province of Santa Elena, produces and markets products of wood, but now states that there a significant drop in sales levels, which have recently been built few customers, business development stopped, getting little recognition in the market, so that arose determine supply and demand for furniture, the diagnosis of the current situation company through SWOT and determining marketing strategies, in addition to the different types of research as descriptive shopping attitudes presented by respondents was determined, he met the manager of the company Mr. Samuel Reyes Suarez in order to obtain information on the marketing of wood products in the research instruments was determined that the economically active population of Santa Elena is 65 262 inhabitants by 2015, with a proportional sample of 382 people to be surveyed obtaining as results that 100% of respondents if they perform furniture purchases timber and 52% of the target shopping is done in Mueblería Samuel Reyes Suarez. So the draft strategic plan is presented to increase sales of the company Mueblería Samuel Reyes Suárez Canton Santa because today there is not a high consumption of products that are sold obtaining intended to increase sales, attract more number of customers, with a renewed corporate image and using strategies of marketing mix, product, price, place and promotion-publicity to allow positional goods in the minds of consumers gaining recognition thereof. Keywords: research, furniture, strategies, marketing.